$$\int \tan^3(2t)\sec^3(2t)\,dt$$

First try:$$\int \tan^3(2t)\sec^3(2t) \, dt=\int (\tan(2t)\sec(2t))^3 \, dt=\int \left(\frac{\sin(2t)}{\cos(2t)}\,\frac{1}{\cos(2t)}\right)^3 \, dt$$


$du=-2\sin(2t) \, dt$

$$-\frac{1}{2}\int \left(\frac{du}{u^2}\right)^3=\frac{1}{2} \cdot \frac{u}{5}^{-5}=\frac{1}{10\cos2t}+C$$

Second Try:

$$\int \tan^3(2t)\sec^3(2t) \, dt=\int \tan^2(2t)\sec^2(2t)\tan(2t)\sec(2t)dt=\int\sec^2(2t)(1-\sec^2(2t))\tan(2t)\sec(2t)$$



$$\frac{1}{2}\int u^2(1-u^2)du=\frac{1}{2}\int u^2-u^4=\frac{u^3}{6}-\frac{u^5}{10}=\frac{sec^{3}(2t)}{6}-\frac{sec^{5}(2t)}{10}+c$$ Where have I got it wrong?

  • $\begingroup$ Start by simplifying your integral by letting $2 t \to x$ and $d t = d x/2$. And it makes no sense to integrate over $(du)^3$. That's your problem. $\endgroup$ – David G. Stork Jan 9 '16 at 22:10
  • $\begingroup$ @DavidG.Stork I need to find integrate according to $dt$ so it is just like $2x$ according to $dx$ $\endgroup$ – gbox Jan 9 '16 at 22:13
  • $\begingroup$ I cannot see why you "need" to integrate according to $dt$. After all, you make a substitution to $du$. Why not first $dx$? $\endgroup$ – David G. Stork Jan 9 '16 at 22:14
  • $\begingroup$ @DavidG.Stork ok so we can replace $dt$ in $dx$ $\endgroup$ – gbox Jan 9 '16 at 22:17

You should not get something like $\left(du \right)^3$ in the espression, it does not make sense. Indeed if you use $du=-2\sin(2t) \, dt$ where $u = \cos 2t$, you get $\sin^2 2t = 1- \cos^2 2t = 1 - u^2$. Put everything into the expression (i.e., express everything in terms of $u$), you get

$$\int \left(\frac{\sqrt{1-u^2}}{u^2}\right)^3 \frac{du}{-2 \sqrt{1-u^2}} = -\frac 12 \int \frac{1-u^2}{u^6} du. $$

Now the right hand side can be evaluated by power rule.

  • $\begingroup$ Added a second try $\endgroup$ – gbox Jan 9 '16 at 22:31
  • 1
    $\begingroup$ @gbox : Looks good, but it should be $u^2 -1$ instead of $1-u^2$, and you are missing some $du$'s. $\endgroup$ – user99914 Jan 9 '16 at 22:38

HINT: show that your integrand is equal to $$8\,{\frac { \left( \sin \left( t \right) \right) ^{3} \left( \cos \left( t \right) \right) ^{3}}{ \left( 2\, \left( \cos \left( t \right) \right) ^{2}-1 \right) ^{6}}} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.